Pemodelan Jaringan Pipa Distribusi Air Minum Berbasis Program WaterGEMS - Syahputra, Ichsan; Irfan, Zu (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Aceh Besar Regency has abundant water resources, but they have not been utilized optimally, especially surface water, one of which is the Krueng Aceh River that crosses Aceh Besar Regency. This is what makes Aceh Besar Regency have the potential for water resources that can be utilized for the daily needs of its people, both for drinking water and other needs, but these efforts have not been achieved optimally and need to be improved in the future through Drinking Water Supply System (SPAM) activities. One of the villages not far from the Krueng Aceh River in Aceh Besar Regency is Ateuk Anggok Village, Ingin Jaya District, Aceh Besar Regency, but currently does not have clean water facilities and infrastructure, especially clean water pipe networks, so that the community only uses underground water sources, namely shallow wells. The title of this research is Modeling of Water Distribution Pipe Network System Based on the WaterGEMS Program. The total length of the planned distribution pipe is 3629.41 m which can distribute clean water to 28 points in the Ateuk Anggok Village area with a total clean water requirement of 0.78 L/second or 0.03 L/second per point. The results of the pipe network modeling with the type and size of the planned pipe diameter obtained a Nominal Pressure (PN) value of 0.98 bars and it is planned to use the HDPE PN10 SDR 17 pipe type. The maximum flow rate that can be passed is 0.84 L/sec while the maximum requirement is 0.78 L/sec, meaning that the planned pipe dimensions are sufficient to meet the maximum water needs. The maximum flow velocity in the pipe network is 0.17 m/sec where the HDPE PN10 type pipe has a maximum permitted speed of 3 m/sec.